1997
DOI: 10.1007/s002449900266
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Transport of Chlordane and Nonachlor Associated with Suspended Sediment in the Mississippi River, May 1988 to June 1990

Abstract: Technical chlordane, a formerly widely used organochlorine pesticide, has become widespread in the environment. The distribution of technical chlordane in riverine environments may be due in part to resuspension and aqueous transport of contaminated bed sediment. To test this hypothesis, the Mississippi River was sampled for suspended sediment five times over a two-year period, at up to 17 sites from St. Louis to below New Orleans, including major tributaries. The ratio of chlordane to nonachlor concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the past, researchers investigating contaminant transport along the Mississippi River have used measurements from sites in Southern Louisiana to estimate the pesticide load discharged into the Gulf of Mexico ( ). From the data presented here, we can provide an estimate of the annual amount of toxaphene discharged into the Gulf of Mexico by the Mississippi River.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, researchers investigating contaminant transport along the Mississippi River have used measurements from sites in Southern Louisiana to estimate the pesticide load discharged into the Gulf of Mexico ( ). From the data presented here, we can provide an estimate of the annual amount of toxaphene discharged into the Gulf of Mexico by the Mississippi River.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the ratio of cis-chlordane to trans-chlordane in technical chlordane is 0.79 (Dearth and Hites 1991;Rostad 1997). The cis-chlordane to trans-chlordane ratios were around 0.79 dominantly in waters, sediments, and soils both in the underground river and in the surface systems, which indicate that the sources were derived from commercial chlordane in waters, sediments, and soils (Fig.…”
Section: Seasonal Variations Of Ocps In Different Samplesmentioning
confidence: 82%
“…The ratio of heptachlor to trans-chlordane corresponds to 3.5 in commercial grade heptachlor, while it is 0.5 in commercial grade chlordane (Rostad 1997;Tomlin 1999). Sci (2014Sci ( ) 71:1977Sci ( -1987Sci ( 1981 The ratios of heptachlor to trans-chlordane in groundwaters and surface waters were around 0.5.…”
Section: Seasonal Variations Of Ocps In Different Samplesmentioning
confidence: 99%
“…P ollution of aquatic systems through runoff from agricultural fields is a major environmental problem worldwide. Pesticides both in suspension and incorporated into depositional sediments are considered potential pollutant sources (Rostad, 1997; Gilliom et al, 1999; Schulz and Liess, 2001). Propiconazole (Fig.…”
mentioning
confidence: 99%